Perioperative Strategies to Improve Sinus Surgery Outcomes in Patients with Cystic Fibrosis: A Systematic Review. Issue 1 (14th May 2013) - Crockett, David J.; Wilson, Kevin F.; Meier, Jeremy D.
Abstract : Objectives: Review the literature for intraoperative techniques and postoperative practices after functional endoscopy sinus surgery (FESS) that may improve outcomes in patients with cystic fibrosis (CF). Data Sources: PubMed and the Cochrane Library. Review Methods: A systematic review of the literature was performed. Articles from 1990 to 2012 were searched using the terms sinus surgery and cystic fibrosis with studies limited to the English language and human subjects. Abstracts were reviewed to identify relevant original manuscripts. Bibliographies of relevant articles were examined to identify additional manuscripts. Results: The initial PubMed search identified 169 articles. One additional article was identified through the Cochrane Library. After reviewing the abstracts, 41 selected studies were examined in further detail, and 22 articles were ultimately selected for suitability for this review. The bibliographies of these articles were reviewed and no additional articles were identified. Perioperative strategies included postoperative medical therapies, intraoperative techniques and image guidance, intranasal corticosteroid injection, dornase alfa, gene therapy, and second‐look procedures. Most studies were limited to case series with relatively small numbers of patients. Very few randomized controlled studies were identified. Conclusion: Despite the prevalence of recurrent sinonasal disease after FESS in patients with CF, evidence for definitive perioperative management in this population is lacking. Most recommendations are based on small case series. Multicenter studies to evaluate perioperative strategies that improve FESS outcomes in patients with CF are warranted.